Undergraduate Social Work Students' Perceptions of a Team-Based Learning Approach to Exploring Adult Development. Issue 2 (15th March 2018) - Watkins, Karen; Forge, Nicholas; Lewinson, Terri; Garner, Brittany; Carter, Larance D.; Greenwald, Lindsay
ABSTRACT: Social work educators are challenged to adopt innovative instructional methods and pedagogies to prepare students to meet the contemporary needs of diverse client populations. A team-based learning (TBL) approach is a pedagogical strategy that utilizes cooperative and collaborative learning principles to inspire academic, professional, and interpersonal growth for students. This study explores perspectives of 93 undergraduate social work students regarding the benefits and challenges of using a TBL approach to research adult development. Despite identifying several benefits of this method, including in-depth learning and enhanced relationships, students also experienced significant challenges to working in teams.